La παρρησία chez Isocrate. L’intellectuel et la liberté de parole dans l’Athènes du IVe s. av. J.-C. - Christodoulou, Panos (Tekmeria, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this study we attempt to elucidate the central place of the notion parrhesia in the political thought of Isocrates. We offer the suggestion that Isocrates’ discussion of parrhesia revealed the antidemocratic character of his thought. Mainly in his speeches Areopagiticus and De Paces where he calls into question the rationality of the debate between the demos and it’s leaders, the Athenian author regards freedom of speech, the principle form of democratic equality, as the main reason for the degradation of civic institutions and the adoption by the Athenian demos of a corrupted political language. He defends the principle that true parrhesia can flourish only amongst his very distinguished lectorat, able to seize the basic principles of his ambitious political and philosophical project. This audience emerges through his texts as a political and cultural elite which should be given full control of the city as well as the exclusive privilege to freedom of speech. In that context parrhesia becomes the trait of an aristocratic politeia where an enlightened elite imposes its own political discourses. Isocrates, who remained hostile to the horizontal diffusion of the political discourse and the active participation of the majority in the exercise of power, considers that freedom of speech can be conceived as a positive civic value only if it is exercised by the most illustrious and educated part of athenien society.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->